2015
DOI: 10.1152/ajpcell.00046.2015
|View full text |Cite
|
Sign up to set email alerts
|

Bladder function in mice with inducible smooth muscle-specific deletion of the manganese superoxide dismutase gene

Abstract: Manganese superoxide dismutase (MnSOD) is considered a critical component of the antioxidant systems that protect against oxidative damage. We are interested in the role of oxidative stress in bladder detrusor smooth muscle (SM) in different disease states. In this study, we generated an inducible, SM-specific Sod2(-/-) mouse model to investigate the effects of MnSOD depletion on the function of the bladder. We crossbred floxed Sod2 (Sod2(lox/lox)) mice with mice containing heterozygous knock-in of a gene enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Our results suggest that Ca 2+ influx, Rho kinase activation, and SK channel deactivation may play important roles in the spontaneous contractions in intact bladder strips, whereas only latter two mechanisms may be involved in H 2 O 2 -induced augmentation of spontaneous contractions. Previous studies indicated that excessive accumulation of ROS [ 17 19 , 57 ] and enhanced spontaneous contractions [ 5 , 6 , 14 ] are related to OAB, indicating high levels of ROS may contribute to the enhanced spontaneous contractions. The current study explored the potential mechanisms of the H 2 O 2 -induced augmentation of spontaneous contractions through pharmacological approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that Ca 2+ influx, Rho kinase activation, and SK channel deactivation may play important roles in the spontaneous contractions in intact bladder strips, whereas only latter two mechanisms may be involved in H 2 O 2 -induced augmentation of spontaneous contractions. Previous studies indicated that excessive accumulation of ROS [ 17 19 , 57 ] and enhanced spontaneous contractions [ 5 , 6 , 14 ] are related to OAB, indicating high levels of ROS may contribute to the enhanced spontaneous contractions. The current study explored the potential mechanisms of the H 2 O 2 -induced augmentation of spontaneous contractions through pharmacological approach.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the elevated levels of ROS have been proposed to contribute to OAB [ 17 , 18 ]. More directly, we generated an inducible, smooth muscle-specific manganese superoxide dismutase (MnSOD) gene knockout mouse model recently [ 19 ]. We found the depletion of MnSOD caused oxidative stress in the bladder and the mice presented bladder overactivity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four hour urination behavior measurement was performed using mouse micturition chambers with a wire mesh bottom designed by Med Associates Inc. (St. Albans, VT) (Liu et al, 2015). The mice were placed in the micturition chambers.…”
Section: Methodsmentioning
confidence: 99%
“…A suprapubic catheter was implanted 2 days prior to cystometry (Liu et al, 2015). Under anesthesia, the bladder was exposed and a circular purse string suture of 7-0 silk was used on the dome of bladder.…”
Section: Methodsmentioning
confidence: 99%